Faktor yang Berhubungan dengan Anemia pada Ibu Hamil di UPT Puskesmas Pembina Palembang Tahun 2024 - Indah; Intan Sari; Reffi Dhamayanti (CV. Creative Tugu Pena, 2024)
Anemia in pregnant women is a condition where the number and size of red blood cells or hemoglobin concentration are below the normal limit value, which is <11 gr/dl. The World Health Organization (WHO) reported in 2020 that 41% of pregnant women experienced anemia. Overall, the prevalence of anemia in pregnant women in developed countries is 49% and in developing countries it is 53%. Internal maternal factors related to anemia include the level of knowledge, education, occupation, parity, pregnancy spacing, age and nutritional status of pregnant women. The purpose of the study was to determine the relationship between nutritional status, knowledge and pregnancy spacing simultaneously with anemia in pregnant women at the Pembina Palembang Health Center in 2024. The study design was cross-sectional. The population in this study were all pregnant women in the second and third trimesters at the Pembina Palembang Health Center in the period January-May 2024. A sample of 52 people was taken using the total population technique. The results of the study showed that there was a partial relationship between nutritional status and the incidence of anemia in pregnant women (p value 0.001), there was no partial relationship between knowledge and the incidence of anemia in pregnant women (p value 0.686) and there was a partial relationship between pregnancy spacing and the incidence of anemia in pregnant women (p value 0.000). Health workers are expected to improve anemia prevention and control programs in pregnant women.